An analysis of stylistic elements and challenges of technique and improvisation in three late piano works by Surendran Reddy (1962–2010) - Schoeman, Ben (University of Pretoria, 2021)
Mini Dissertation (MMus (Performance))--Universtity of Pretoria, 2020.